Cytotoxic and molecular effects of captopril on a colon cancer cell-line: an in vitro study - Al-Saady, Teeb Ali; Ibrahim, Ooroba M. S.; Al-Hussaniy, Hany Akeel (Pharmakeftiki, 2025)
Colorectal carcinoma originates from aberrant cellular proliferation within the colonic or rectal mucosa, culminating in malignant neoplastic growth. As of 2018, cancer accounted for approximately 9.6 million deaths worldwide, ranking as the second leading cause of mortality. This study investigates the antiproliferative effects of captopril, an angiotensin-converting enzyme inhibitor, on the SW480 colorectal adenocarcinoma cell line. SW480 cells were treated with increasing concentrations of cisplatin (15.6–500 µg/mL) and captopril (31.25–1,000 µg/mL), administered both individually and in combination. Cisplatin achieved maximal cytotoxicity at 62.5 µg/mL, whereas captopril required 2,000 µg/mL in order to elicit a comparable effect. The most pronounced anticancer synergy was observed with a captopril / cisplatin combination at 31.25 / 15.6 µg/mL, thereby indicating enhanced chemotherapeutic efficacy through drug interaction. Real-time PCR analysis of PIK3CA gene expression revealed a concentration-dependent transcriptional response. The highest levels of PIK3CA upregulation occurred at 250 µg/mL for cisplatin, 62.5 µg/mL for captopril, and 20 / 1000 µg/mL for their combination. PIK3CA, a key oncogene implicated in cellular proliferation and survival, exhibited significant modulation across the herein examined treatment conditions. These findings underscore captopril’s potential as a novel adjuvant in colorectal cancer therapy, capable of influencing critical oncogenic pathways and amplifying the cytotoxic effects of standard chemotherapeutic agents.